Systems Development of a Two-Axis Stabilised Platform to Facilitate Astronomical Observations - Hepworth, James Haydn (Department of Mechanical Engineering, 2019)
Inertially Stabilised Platforms (ISPs) aim to control the line-of-sight between a sensor and a target. They perform two distinct operations; keeping track of the target as the sensor host and the target move in inertial space and attenuating rotational disturbances incurred to the sensor by host vehicle motion. This project aimed to develop a two-axis ISP for use in astronomical applications. It represents the initial development of all systems of a low-cost ISP designed for a 3.5” compound telescope. To achieve this, relevant literature describing the various components of an ISP were reviewed to inform the design, implementation and testing cycle which comprised most of the project. A set of system specifications was developed to guide design decisions. The performance of the implemented system was compared against these specifications once the project was complete. During the project, the electro-mechanical structure of the ISP was designed and implemented, including a mechanical assembly designed to mount a camera and inertially and geometrically model the specified telescope. This allowed the ISP to be tested at a lower cost than with the telescope itself. The associated electrical systems were specified and configured. An image processing script capable of detecting and locating the centre of the Moon in the camera field of view was written in Python and implemented on a Raspberry Pi Computer. A complete simulation model for the system was written in the simulation language, Simul_C_EM, and used to design various controllers for the ISP control system and help verify certain estimated system parameters such as gimbal friction. For each gimbal, PI controllers were designed to allow manual orientation control of the telescope, compensated P controllers were designed to achieve target tracking, and compensated PI controllers were designed to reject rotational disturbances. These were implemented in C on an STM32F0 microcontroller tasked with managing the various control and communications tasks required by the system. Finally, a user interface was written in LabVIEW to facilitate intuitive user control of the system and perform datalogging of the system runtime data. Testing of the system showed good correlation between the hardware and the simulated results indicating an accurate simulation model that can be used to test future design developments.